Evaluating the Utility of Plain Radiograph and Computerised Tomography Scanning in Identifying Concomitant Foot Fractures in Patients with Unstable Lisfranc Injuries - Junaid Aamir MBChB MRes MRCS; Robyn Caldwell MBChB; Dileep Karthikappallil MBChB MRCSed; Mamdouh M. Elbannan MRCS, MCh Orthopaedic; Hiro Tanaka MSc FRCS (TrOrth); Lyndon W. Mason FRCS (Tr&Orth) (Foot & Ankle Orthopaedics, 2023)
Category: Midfoot/Forefoot; Trauma Introduction/Purpose: Lisfranc fracture dislocations are uncommon injuries, which frequently require surgical intervention. Currently, there is varying evidence on the diagnostic utility of plain radiographs (XR) and CT in identifying Lisfranc injuries and concomitant fractures. Our aim was to identify the utility of XR as compared to CT, with the nul hypothesis that there was no difference in fracture identification. Methods: A retrospective assessment of patients who had sustained a Lisfranc injury between 2013 and 2022 across two trauma centres within the United Kingdom who underwent surgery. Pre-operative XR and CT images were reviewed independently by 2 reviewers to identify the presence of associated fractures. Results: A total of 175 patients were included. Our assessment identified that XR images significantly under-diagnosed all metatarsal and midfoot fractures. The largest discrepancies between XR and CT in their rates of detection were in fractures of the cuboid (5.7% vs 28%, p< 0.001), medial cuneiform (20% vs 51%, p=0.008), lateral cuneiform (4% vs 36%, p=0.113), second metatarsal (57% vs 82%, p< 0.001), third metatarsal (37% vs 61%, p< 0.001) and fourth metatarsal (26% vs 43%, p< 0.001). As compared to CT, the sensitivity of XR was low. The lowest sensitivity for identification however was lateral foot injuries, specifically fractures of the lateral cuneiform (sensitivity 7.94%, specificity 97.3%), cuboid (sensitivity 18.37%, specificity 99.21%), fourth (sensitivity 46.7%, specificity 89.80%) and fifth metatarsal (sensitivity 45.00%, specificity 96.10%). Conclusion: From our analysis, we can determine that XR significantly under-diagnoses associated injuries in patient sustaining an unstable Lisfranc injury, with lateral foot injuries being the worst identified. We advised the use of CT imaging in all cases for appropriate surgical planning.